Bringing diversity back to agriculture: Smaller fields and non-crop elements enhance biodiversity in intensively managed arable farmlands. (July 2018) - Šálek, Martin; Hula, Vladimír; Kipson, Marina; Daňková, Renata; Niedobová, Jana; Gamero, Anna
Highlights: We studied the effect of habitat heterogeneity on biodiversity in arable-dominated farmland. Smaller patch sizes and non-cropped elements were related to higher farmland biodiversity. Butterflies were good indicator of overall biodiversity. Promoting heterogeneity may be successful in protecting farmland biodiversity. Abstract: Agricultural intensification has substantially reduced multi-scale habitat heterogeneity, including increased field size and loss of semi-natural structures, thus resulting in large-scale deterioration of farmland biodiversity. Biodiversity conservation in farmland has therefore become a conservation priority on a regional as well as continental scale. The effect of habitat heterogeneity on biodiversity on different trophic and niche levels is poorly understood, particularly in agricultural regions with simple arable patterns, where biodiversity has declined most conspicuously. To investigate the effects of habitat heterogeneity on biodiversity in an intensively managed arable-dominated agricultural landscape, we measured the abundance and species richness of spiders, butterflies, birds and European hares as well as the fine-scale habitat composition on various spatial scales. Additionally, we examined correlations between species richness and abundance among taxonomic groups to investigate if any of the biodiversity parameters provided a good indicator of overall farmland biodiversity. We found that smaller patch sizes and larger areas of non-cropped elements (margins, hedges and grasslands) were related to higher farmland biodiversity of different taxonomic groups but habitat diversity was not. The positive effect of these factors was recorded on both spatial scales and in a separate analysis considering groups with different habitat requirements and dispersal abilities. Biodiversity parameters (i.e. species richness and abundance) of the taxonomic groups were positively correlated with one another. In particular, butterfly species richness correlated with bird, butterfly and spider abundance and with bird species richness, suggesting that it may be a good indicator of general farmland biodiversity in intensively managed arable landscapes. Our results suggest that enhancing the heterogeneity of farmed landscapes by decreasing field size and increasing the availability of non-cropped habitats may be a valuable tool for conserving farmland biodiversity in intensive arable farmlands.